The RxPinoy health directory. (Manila Infomediary Philippines, 2002)
It has names and contact numbers of Metro Manila-based physicians and allied health professionals arranged in its specialty index. It also contains a list of Metro Manila hospitals and health centers. It also contains an index of Filipino surgeons on the net.
Keywords: Medical care -- Philippines -- Directories; Physicians -- Philippines -- Manila Metropolitan Area -- Directories; Hospitals -- Philippines -- Manila Metropolitan Area -- Directories